Additions to the Marine bivalve mollusks of Peru - Paredes, Carlos (2003)
The following species of marine bivalve mollusks were recorded for the first time from the Peruvian sea: Glycymeris (Axinactus) delessertii (Reeve, 1843); Botula cylista Berry, 1959; Parahyotissa (Pliohyotissa) quercinus (Sowerby II, 1871); Pitar (Pitar) helenae Olsson, 1961; Eurhomalea lenticularis (Sowerby I, 1835); and Cardiomya planetica (Dall, 1908). Description, habitat and the geographical distribution are cited for each species.